Fusion of holistic and local features for palmprint recognition - Siti Nur Wasilah Mohd Zuki author (School of Computer and Communication Engineering, 2018)
This research project used palmprint image for person identification. The scope of this project is to extract features from holistic and local features using Gabor filter bank and Discrete Cosine Transform (DCT) respectively. To perform the matching process, Euclidean distance classifier is needed to achieve maximum accuracy. The proposed algorithms are implemented using MATLAB software. The algorithm is modelled using m code. The entire algorithms are tested using the benchmark PolyU palmprint dataset developed by Hong Kong Polytechnic University that is widely used in many palmprint recognition (Younesi & Amirami, 2017).